Transfer of Higher Education Policies in East Africa. Analysing the Policy Process Through the Lens of State-Building - (:unkn) unknown (My University, 2015)
Higher education reforms in northern and southern countries seem to be characterised by similar policy processes. The transformations of higher education institutions are usually presented as an outcome of the increasing pressure of international organisations and the success of global policy transfers, especially in countries depending on foreign aid. However this dissertation aims to critically analyse these reform processes through an original and comparative framework. Basing on the case study of four public universities in East Africa, our empirical evidence demonstrates that these higher education institutions are constantly shaped by singular policy configurations, for instance in the decision-making process or during the implementation of the cost-sharing policy. We argue that this original result can be explained by a two-way relationship between public policy analysis and the state-building framework. Therefore we argue that policy processes like the success and failure of global policy transfers or the network of involved stakeholders can only be studied through the theoretical articulation of public policy analysis and the historical sociology of state formation.
Keywords: African Research